Emergence of a novel porcine pestivirus with potential for cross-species transmission in China, 2023 - Li-shuang Deng; Tong Xu; Zhi-wen Xu; Ling Zhu (Veterinary Research)
Abstract Pestiviruses, RNA viruses belonging to the Flaviviridae family, have a broad host range. Their pathogenicity varies greatly and they have caused significant economic losses in animal husbandry. In this study, a novel pestivirus, porcine abortion-associated pestivirus (PAAPeV), was isolated from pigs in China in 2023. Clinically, PAAPeV causes abortions in sows and leads to congenital tremors and death in piglets. PAAPeV replicates efficiently in ST cells. Morphologically, PAAPeV virions are spherical particles with a diameter of approximately 80 nm. Phylogenetic analysis reveals that PAAPeV is closely related to Wenzhou Pipistrellus abramus pestivirus and clusters into a distinct branch, suggesting that it represents a new species: Pestivirus chinensis. Animal experiments demonstrated that PAAPeV-infected piglets and mice exhibit significant histopathological changes. In piglets, histopathological examination revealed myocarditis, hepatitis, glial vacuolation and cerebrovascular inflammation. In mice, findings included hepatic monocyte aggregation, glomerular atrophy, pulmonary edema, inflammatory cell infiltration, and capillary dilation. Viremia has been detected in both piglets and mice, with high viral genome loads found in various organs. In vitro results revealed that PAAPeV replicates in ST cells and, to a lesser extent, in human (A549 and HepG2) and monkey (Vero) cells. Overall, PAAPeV infects both pigs and mice and has the potential to infect other mammals, indicating its ability for cross-species transmission. This poses significant risks to the pig industry and public health. Strengthening monitoring and prevention efforts for PAAPeV is crucial. Our findings greatly increase the understanding of pestivirus diversity and its broader pathogen spectrum.